THREE NEWSPAPERS’ COVERAGE OF INTIMATE PARTNER VIOLENCE AGAINST WOMEN IN NIGERIA, 2015-2017 - Agbese, Aje-Ori (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
This article explores how three national newspapers cover the cases of intimate partner violence against women (IPVAW) in Nigeria from 2015 to 2017 to contribute to global research on mediated representations of violence against women. The study focuses on how Nigerian newspapers, The Guardian, Punch and Vanguard, reported the IPVAW cases from 2015 to 2017, and how they covered and framed IPVAW. Using quantitative content analysis, we found that the newspapers used episodic framing, blamed the victims, and exonerated/ excused the men’s actions. The implications of these findings are discussed. To cite this article (7th APA style):Agbese, A. O. (2021). Three Newspapers’ Coverage of Intimate Partner Violence against Women in Nigeria, 2015-2017. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 12-25. http://dx.doi.org/10.36782/jcs.v1i1.2057